Online voting system (ovs) on server site - Mohammad Haeri, Jaiman (2013)
This paper presents the online voting system pleasant voters to vote wherever they live. It can easily implement and carry out a variety of parallel voting event and can be used for small scale in vote candidates for faculty as well as large as scale election MPP. Online voting system only allows voters to enter vote once in an election. The voters whose qualifications to vote are allowed to register and vote in the election. After that, the votes of voters will be calculated and display to the public at all times the selection of a candidate.